Systematic Literature Review about Exploring the Relationship of Cross-border E-commerce and China's Foreign Trade Based on Different Models - Cao, Wang; Putit, Lennora (Advances in Social Sciences Research Journal, 2023)
The proportion of Chinese cross-border e-commerce in China's foreign trade has gradually increased in recent years. In the last few years, scholars have used different empirical test models such as the trade gravity model and coupling model to empirically test whether cross-border e-commerce can promote China's foreign trade from different perspectives. Based on researching and collating the academic journals in Chinese National Knowledge Infrastructure, this paper sorts out and reviews relevant literature studying relationship between cross-border e-commerce and China's foreign trade. Through the trade gravity model, the mutual promotion relationship between the development of cross-border e-commerce and China's foreign trade has been verified. The coupling model has also made clear of the fact that the coupling degree of the two systems has to be improved so as to continuously promote the development of cross-border e-commerce. On account of the existing researches, the new directions and prospects of future research are put forward in order to facilitate future researchers to better delve into the related topics of the interrelationship between cross-border e-commerce and the Chinese foreign trade economy.